Does Emotionality Prevail Over Rationality? Evaluating The Dynamics of Human Cognitions and Affections in Hotel Service Satisfaction - Boishampayan Chatterjee; Rimi Moitra (Centre For Tourism Planning and Development, 2022)
This paper attempts to measure the relative importance of cognitive and affective factors in the context of hotel service satisfaction. Although the literature talks about the relative influence of cognitive and affective factors on satisfaction, it is generally mute on the “Impact Overlap” that may exist due to the simultaneity of the influence. The confoundedness created by this impact overlap is the research gap, which this paper tries to disentangle. Principal Component Analysis has been used to construct cognitive and affective indices based on the factors identified from the previous literature. The relative importance of the cognitive and affective factors that a consumer considers while deciding to stay in a hotel is assessed using regression analysis. Our findings from the regression analyses suggest that cognitive factors such as infrastructure and location significantly increases customer service satisfaction. Amongst the affective factors, personalization and word of mouth have a significant positive impact on service satisfaction, even after controlling for brand name. Furthermore, results from the regressions testing the interaction effect of cognitive and affective factors reveal that for customers valuing affective factors, the impact of cognitive factors on satisfaction is relatively less. However, the converse is not necessarily true. This finding therefore implies that affective factors play a relatively important role than cognitive factors in deriving service satisfaction.